2022
DOI: 10.1111/mmi.14850
|View full text |Cite
|
Sign up to set email alerts
|

Small RNAs that target G‐rich sequences are generated by diverse biogenesis pathways in Epsilonproteobacteria

Abstract: Bacterial small RNAs (sRNAs) are widespread post‐transcriptional regulators that control bacterial stress responses and virulence. Nevertheless, little is known about how they arise and evolve. Homologs can be difficult to identify beyond the strain level using sequence‐based approaches, and similar functionalities can arise by convergent evolution. Here, we found that the virulence‐associated CJnc190 sRNA of the foodborne pathogen Campylobacter jejuni resembles the RepG sRNA from the gastric pathogen Helicoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 110 publications
(166 reference statements)
0
10
0
Order By: Relevance
“…In general, our “standard” C. jejuni Ribo-seq dataset successfully differentiated between known coding and non-coding regions. For example, cDNA reads for the sRNA CJnc180 (Dugar et al, 2013; Svensson and Sharma, 2022, 2021) were mainly restricted to the RNA-seq (transcriptome) library prepared in parallel, while the adjacent ORF Cj1650 had both RNA-seq and Ribo-seq coverage ( Fig. 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, our “standard” C. jejuni Ribo-seq dataset successfully differentiated between known coding and non-coding regions. For example, cDNA reads for the sRNA CJnc180 (Dugar et al, 2013; Svensson and Sharma, 2022, 2021) were mainly restricted to the RNA-seq (transcriptome) library prepared in parallel, while the adjacent ORF Cj1650 had both RNA-seq and Ribo-seq coverage ( Fig. 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…While we found that CJnc180 was not required for CJnc190 processing, several C. jejuni and C. coli strains express this antisense RNA ( Dugar et al, 2013 ; Riedel et al, 2020 ; Svensson and Sharma, 2021 ), suggesting it has a conserved function. Because of its extensive complementarity to CJnc190, as well as its co-processing, we hypothesized that it might serve as a CJnc190 antagonist and indirectly affect ptmG regulation.…”
Section: Resultsmentioning
confidence: 52%
“…Thus, CJnc190 binding likely interferes with translation initiation, resembling the canonical mode of sRNA-mediated target repression ( Storz et al, 2011 ). The structure of mature CJnc190 is reminiscent of RepG sRNA from Helicobacter pylori ( Svensson and Sharma, 2021 ), which uses a C/U-rich loop to target a phase-variable G-repeat in the 5’ UTR of a chemotaxis receptor mRNA ( Pernitzsch et al, 2014 ). Although CJnc190 and RepG share C/U-rich loop regions, their biogenesis is strikingly different: while RepG is transcribed as a separate standing gene corresponding to the mature sRNA ( Pernitzsch et al, 2014 ), CJnc190 is transcribed opposite to another sRNA (CJnc180) and is processed into the mature form from diverse precursors in C. jejuni and related C. coli ( Svensson and Sharma, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly-cytosine stretches, such as in FoxJ, are often found in bacterial sRNAs and might represent a hallmark of regulatory RNAs in bacteria with low GC content genomes such as F. nucleatum ( 38 , 39 ). In fact, FoxJ’s companion sRNA FoxI uses a C-stretch to repress the translation of its targets ( 8 , 25 ).…”
Section: Discussionmentioning
confidence: 99%